The effects of genre on the lexical richness of argumentative and expository writing by Chinese EFL learners - Heng, Renquan; Pu, Liping; Liu, Xing (Frontiers in Psychology, 2023)
Lexical richness, a crucial aspect of L2 writing research, has been shown to make a difference in L2 writing performance. Nonetheless, the majority of empirical studies have focused either on a single text type or on the comparison between narrative and non-narrative writing (mostly argumentative writing) in academic contexts, whereas there has been a dearth of research regarding the lexical features pertaining to varied non-narrative writing genres. Considering the cognitive demands intrinsic in different writing task types, this study examined the development of lexical richness, which includes lexical density, lexical variation, and lexical sophistication, in Chinese EFL students’ argumentative and expository compositions over the course of one academic year. Fifty-four participants were asked to write eight compositions (in two alternating genres)—four argumentative and four expository—which were parsed using two computational tools. The results indicated a significant increase in all three subconstructs of lexical richness in argumentative compositions over the year, while in expository compositions, only lexical density and lexical sophistication demonstrated an increasing trend. As time went on, the participants in both genres tended to use more high-frequency words with more senses, more academic words, more high-frequency bigrams, and words that are less familiar and more precise. Moreover, the argumentative compositions displayed higher lexical density than the expository ones, while the expository compositions manifested greater lexical variation and lexical sophistication than the argumentative ones. The findings of the study suggest some implications for L2 writing teaching and research.